The Cancer Prevention Study-3 FFQ Is a Reliable and Valid Measure of Nutrient Intakes among Racial/Ethnic Subgroups, Compared with 24-Hour Recalls and Biomarkers. Issue 3 (20th January 2021) - McCullough, Marjorie L; Wang, Ying; Hartman, Terryl J; Hodge, Rebecca A; Flanders, W Dana; Stevens, Victoria L; Sampson, Laura; Mitchell, Diane C; Patel, Alpa V
ABSTRACT: Background: Valid assessment of dietary intake in diverse populations is important for studies of chronic disease risk in the United States. Objectives: We evaluated the reproducibility and validity of a food frequency questionnaire (FFQ) modified for the American Cancer Society's Cancer Prevention Study-3 (CPS-3) prospective cohort, among a racially/ethnically diverse subgroup. Methods: The Diet Assessment Substudy included 677 CPS-3 participants (64% women; 61% non-Hispanic white, 24% non-Hispanic black, 15% Hispanic), aged 31–70 y, who completed 2 FFQs 1 y apart (FFQ1, FFQ2), 4–6 telephone-administered 24-h dietary recalls (24HRs), and 2 fasting blood samples and 24-h urine collections ∼6 mo apart in the interim. Spearman rank correlation coefficients (ρ) were used to evaluate FFQ reproducibility and validity compared with 24HRs for 67 nutrient exposures. For 18 of these nutrients, we used the method of triads to calculate validity coefficients (VCs, ρ) from pairwise correlations of FFQ2, 24HRs, and biomarkers. Analyses were stratified by sex, race/ethnicity, education, and BMI. Results: Mean (range) FFQ reproducibility correlations were ρ = 0.65 (0.50–0.91) for men and ρ = 0.63 (0.37–0.89) for women; mean (range) energy-adjusted, deattenuated correlations of FFQ2 with 24HRs were ρ = 0.60 (0.33–0.84) for men and ρ = 0.55 (0.21–0.79) for women. FFQ2 VCs (ρ) among men ranged from 0.42 for β-cryptoxanthin to 0.91 for omega-3 (n–3) fatty acids and, among women, from 0.41 for sodium to 0.79 for total vitamin D. Mean FFQ reproducibility and validity were highest among whites (ρ = 0.68, ρ = 0.58, respectively) and slightly lower among blacks (ρ = 0.57, ρ = 0.49, respectively) and Hispanics (ρ = 0.59, 0.55, respectively). FFQ reproducibility and validity were slightly lower among those with less than a 4-y college degree, and those with a BMI ≥30 kg/m 2 . Conclusions: Reproducibility and validity of the CPS-3 FFQ were comparable with similar studies for most nutrients, among all subgroups. These findings support future dietary analyses in the contemporary CPS-3 cohort and other similar cohorts.